Evaluating the Influence of Environmental Factors on Mountain Stream Nitrate Concentrations in Miyazaki Prefecture - MAKINO, Soyoka; MAUNG, Nay Lin; TOKUCHI, Naoko (Journal of Environmental Conservation Engineering, 2022)
Long-term nitrogen (N) loading on forest ecosystems can lead to "N-saturated forests". Such ecosystems are likely to have high stream nitrate (NO3-) concentrations. Recent increases in atmospheric emissions from livestock and agriculture activities and combustion of fossil fuels have changed the N cycle in terrestrial ecosystems. We investigated stream NO3- concentrations from 200 forest catchments free from human disturbances within Miyazaki Prefecture and assessed the relationships with N depositions and catchment properties (e.g., climate, topography, vegetation, geology, and soil). Stream NO3- concentration ranging from 0.01-1.07 ㎎ N L-1 indicating that factors controlling stream NO3- concentration were variable. High NO3- concentrations were more common for sites with low annual precipitation, high ammonia emission-based N depositions from livestock and agriculture, and high annual N deposition. Temperature, elevation, and radiation are also important factors. Our study is the first to show the influence of livestock and agriculture via N deposition on mountain stream chemistry in Japan.